(untitled) (Comprehensive Journal of Science, 2026)
The advantages and disadvantages of using gallium nitride (GaN) in comparison with other semiconductor materials of microelectronics are described. It is shown that the high thermal, chemical, and radiation resistance of GaN makes it possible to manufacture devices operating at elevated temperatures and under extreme conditions, while high thermal conductivity simplifies cooling of the active region. The combination of high electron mobility and a high breakdown electric field makes GaN suitable for manufacturing high-power, high-frequency, and high-temperature transistors. Design solutions and technological methods for forming GaN-based devices are presented.